Being uncertain in thin layer chromatography—Some thoughts about latent details in the retention estimation. Issue 6 (3rd April 2018) - Komsta, Łukasz
ABSTRACT: This paper deals with some important (but often neglected) details about the uncertainty of retention measurement in thin layer chromatography, the propagation of uncertainty during computing simple and more complex values from the retention data, ending in influence of the retention uncertainty onto the regression estimates during extrapolation and lipophilicity estimation. Theoretical considerations are tested on data from previous study. It can be concluded that when TLC spots are broad and the retention uncertainty exceeds about 0.02 of R F value, the uncertainty should be taken into the account in further computations. GRAPHICAL ABSTRACT: